Experimental study on laboratory scale Totalized Hydrogen Energy Utilization System using wind power data. (11th May 2017) - Bhogilla, Satya Sekhar; Ito, Hiroshi; Segawa, Takehiko; Kato, Atsushi; Nakano, Akihiro
Abstract: The renewable energy source like wind energy generates electric power with intermittent nature. Hydrogen energy system can help to solve the fluctuation problem of the wind power. Totalized Hydrogen Energy Utilization System (THEUS) consists of a Unitized Reversible Fuel Cell (URFC), a hydrogen storage tank, and other auxiliary components. Wind power is inherently variable; the URFC will be subjected to a dynamic input power profile in water electrolyzer mode operation. This paper describes the THEUS operation and performance at different variations in intermittent wind power. The performance of the THEUS was evaluated in water electrolyzer and fuel cell mode operation. The stack efficiency, system efficiency, and system efficiency including heat output from the URFC were presented at each operation. The total efficiency of the URFC and THEUS were also investigated. The maximum total efficiency of the URFC and THEUS were 53% and 66%, respectively. Highlights: A Totalized Hydrogen Energy Utilization System (THEUS) was tested. Adaptability of the THEUS for the intermittent wind power was investigated. Several efficiencies of the THEUS were estimated at each operation. The performance of the stack increased at low current densities in fuel cell mode. The contribution of heat recovery for total efficiency was shown quantitatively.